2019
DOI: 10.1371/journal.pone.0216873
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic based biosensor for rapid detection of Salmonella in food products

Abstract: An impedance based microfluidic biosensor for simultaneous and rapid detection of Salmonella serotypes B and D in ready-to-eat (RTE) Turkey matrix has been presented. Detection of Salmonella at a concentration as low as 300 cells/ml with a total detection time of 1 hour has been achieved. The sensor has two sensing regions, with each formed from one interdigitated electrode array (IDE array) consisting of 50 finger pairs. First, Salmonella an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…1 demonstrates the numerical domain and boundaries. Since variation of velocity in the span wise direction of this channel is negligible (due to negligible side wall effects on sensor surface), 2D simulation is valid for this case ( Liu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 demonstrates the numerical domain and boundaries. Since variation of velocity in the span wise direction of this channel is negligible (due to negligible side wall effects on sensor surface), 2D simulation is valid for this case ( Liu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another common numerical study reported for this application is based on using an analytical velocity profile (assuming fully developed Poiseuille flow) in the convective-diffusive transport equation instead of using the converged velocity from Navier-stokes equations. Gelarkin finite-element method ( Selmi et al, 2017 ) and COMSOL commercial code ( Hu et al, 2007 ; Liu et al, 2019 ), (including FEMLAB, MATLAB subsidiary of COMSOL) are in this category, in which it has been reported that numerical results has more than 2 orders of magnitude difference with the experimental data ( Squires et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, much effort has been focused on novel sample pretreatment methods that are potential to be integrated into biosensors, including IMS (Du et al., 2018), microfluidic separation (He et al., 2013; Liu et al., 2019; Srbova et al., 2018), electrophoresis (Nguyen, Nguyen, Bui, & Seo, 2019; Zhang, Luo, et al., 2018), acoustophoresis (Ngamsom, Lopez‐Martinez, et al., 2016), magnetophoresis (Ngamsom, Esfahani, et al., 2016), and magnetic ionic liquid‐based extraction (Hice, Clark, Anderson, & Brehm‐Stecher, 2019). Among them, IMS has been regarded as one of the most useful tools for selective capture, separation, and concentration of Salmonella prior to detection.…”
Section: Challenges In the Development Of Salmonella Biosensorsmentioning
confidence: 99%
“…Much has been done in all of these challenges, as can be easily confirmed in the recent literature for various types of biosensors (see e.g. some review papers) [ [1] , [2] , [3] , [4] , [5] ]. However, this considerable body of knowledge has not been transformed into products for various reasons, the most important of which is perhaps the high cost of device engineering to develop tests and certify them through government agencies.…”
Section: Introductionmentioning
confidence: 97%